New Treatment Approach in Indian Visceral Leishmaniasis: Single-Dose Liposomal Amphotericin B Followed by Short-Course Oral Miltefosine - Sundar, Shyam; Rai, M.; Chakravarty, J.; Agarwal, D.; Agrawal, N.; Vaillant, Michel; Olliaro, Piero; Murray, Henry W. (Clinical infectious diseases, 2008)
Background. In Bihar, India, home to nearly one-half of the world's burden of visceral leishmaniasis, drug resistance has ended the usefulness of pentavalent antimony, which is the traditional first-line treatment. Although monotherapy with other agents is available, the use of 2 drugs with different modes of action might increase efficacy, shorten treatment duration, enhance compliance, and/or reduce the risk of parasite resistance. To test the feasibility of a new approach to combination therapy in visceral leishmaniasis (also known a kala-azar), we treated Indian patients with a single infusion of liposomal amphotericin B (L-AmB), followed 1 day later by short-course oral miltefosine. Methods. We used a randomized, noncomparative, group-sequential, triangular design and assigned 181 subjects to treatment with 5 mg/kg of L-AmB alone (group A; 45 subjects), 5 mg/kg of L-AmB followed by miltefosine for 10 days (group B; 46 subjects) or 14 days (group C; 45 subjects), or 3.75 mg/kg of L-AmB followed by miltefosine for 14 days (group D; 45 subjects). When it became apparent that all regimens were effective, 45 additional, nonrandomized patients were assigned to receive 5 mg/kg of L-AmB followed by miltefosine for 7 days (group E). Results. Each regimen was satisfactorily tolerated, and all 226 subjects showed initial apparent cure responses. Nine months after treatment, final cure rates were similar: group A, 91% (95% confidence interval [CI], 78%–97%]; group B, 98% (95% CI, 87%–100%); group C, 96% (95% CI, 84%–99%]; group D, 96% (95% CI, 84%–99%); and group E, 98% (95% CI, 87%–100%). Conclusions. These results suggest that treatment with single-dose L-AmB followed by 7–14 days of miltefosine is active against Indian kala-azar. This short-course, sequential regimen warrants additional testing in India and in those regions of endemicity where visceral leishmaniasis may be more difficult to treat. Trial registration. ClinicalTrials.gov identifier: NCT00370825.